A SYSTEMATIC REVIEW OF FORMATIVE ASSESSMENT IN HIGH SCHOOL PHYSICS LEARNING - Siti Nurjanah; Slamet Suyanto; Muhammad Iqbal; Shaufi Ramadhani; Izzul Kiram Suardi; D’aquinaldo Stefanus Fani Seran (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
Implementing formative assessment (FA) in physics learning has been widely acknowledged as an effective strategy for enhancing learning process and student performance. Unfortunately, there was a dearth of thorough research on formative assessment in high school physics learning, including publication opportunities, physics topics evaluated by prior studies, and forms of formative assessment investigated by prior studies. This review mapped studies on formative assessment in physics subjects in the high school context. The research method used was a systematic review by analyzing relevant research results from the Scopus databases that published over the past decade (from 2014 to 2023). A total of 17 articles were examined in this study. This study found that Q1 ranked journals were where the most articles with FA topics in high school physics subjects were published. Mechanics was the most common physics topic investigated by previous research. Technology-based formative assessment was the most common form of FA used by previous studies. The results of this review may benefit researchers, school leaders, and policy makers when they aspire to do research or facilitate the implementation of formative assessment in physics class.